2017
DOI: 10.1007/s10456-017-9539-8
|View full text |Cite
|
Sign up to set email alerts
|

ETS transcription factors Etv2 and Fli1b are required for tumor angiogenesis

Abstract: ETS transcription factor ETV2 / Etsrp functions as a key regulator of embryonic vascular development in multiple vertebrates. However, its role in pathological vascular development has not been previously investigated. To analyze its role in tumor angiogenesis, we utilized a zebrafish xenotransplantation model. Using a photoconvertible kdrl:NLS-KikGR line we demonstrated that all tumor vessels originate from the existing embryonic vasculature by the mechanism of angiogenesis. Xenotransplantation of mouse B16 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
(54 reference statements)
2
18
0
Order By: Relevance
“…ETV5 has also been shown to trigger the transcription of MMP‐2, TIMP, and other proteinases to modify the extracellular matrix in human chondrosarcoma . Additionally, previous studies have indicated that other ETS members, such as ETS1, ETS2, ETV2 and ETV4 regulate tumor angiogenesis . Our study showed that ETV5 can regulate angiogenesis in the context of CRC.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…ETV5 has also been shown to trigger the transcription of MMP‐2, TIMP, and other proteinases to modify the extracellular matrix in human chondrosarcoma . Additionally, previous studies have indicated that other ETS members, such as ETS1, ETS2, ETV2 and ETV4 regulate tumor angiogenesis . Our study showed that ETV5 can regulate angiogenesis in the context of CRC.…”
Section: Discussionsupporting
confidence: 58%
“…28 Additionally, previous studies have indicated that other ETS members, such as ETS1, ETS2, ETV2 and ETV4 regulate tumor angiogenesis. [29][30][31] Our study showed that ETV5 can regulate angiogenesis in the context of CRC. Importantly, ETV5 and its direct target, PDGF-BB, tend to be co-overexpressed in CRC, and CRC with both genes upregulated exhibits the worst prognosis ( Fig.…”
Section: Discussionmentioning
confidence: 63%
“…The ETS transcription factors ETV2, FLI1, and ERG1 act early to specify pluripotent cells toward the EC lineage (24). ETV2 alone drives vasculogenesis, whereas ETV2 and FLI1 act redundantly during angiogenesis (25). ERG1 promotes vascular differentiation and stability through Wnt/ß-catenin signaling (26).…”
Section: Transcriptional Regulation Of Ec Specification and Differentmentioning
confidence: 99%
“…E26 transformation-speci c variant 5 (ETV5), a member of the ETS family, has been reported to be involved in the progression of hematologic malignancies, endometrial cancer [11,12], ovarian cancer [13,14], prostate cancer and thyroid cancer [15,16]. Some previous studies also revealed that the ETS family triggered angiogenesis in multiple tumors [13,17,18]. Similarly, our previous study showed that ETV5 facilitated CRC angiogenesis via PDGF-BB/Src/STAT3/VEGFA signaling pathway [19].…”
Section: Introductionmentioning
confidence: 84%